2016
DOI: 10.1097/mop.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

The tooth exposome in children's health research

Abstract: Purpose of review The exposome concept proposes a comprehensive assessment of environmental exposures from the prenatal period onwards. However, determining exposure timing especially over the prenatal period is a major challenge in environmental epidemiologic studies. Recent findings For decades teeth have been used to estimate long-term cumulative exposure to metals. Recently developed high-dimensional analytical methods that combine sophisticated histological and chemical analysis to precisely sample toot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 87 publications
(94 reference statements)
0
41
0
Order By: Relevance
“…The strength of the study is the advanced methodology of using teeth Mn biomarkers allowing us to study early human development in a unique and non-invasive manner. Tooth Mn measures have been validated in human and animal studies and are a direct fetal biomarker of exposure (Andra et al, 2016). Having multiple time points of fetal exposure, as opposed to a single measure, allowed us to uncover developmental stage specific differences in Mn uptake across genotypes, something that has not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the study is the advanced methodology of using teeth Mn biomarkers allowing us to study early human development in a unique and non-invasive manner. Tooth Mn measures have been validated in human and animal studies and are a direct fetal biomarker of exposure (Andra et al, 2016). Having multiple time points of fetal exposure, as opposed to a single measure, allowed us to uncover developmental stage specific differences in Mn uptake across genotypes, something that has not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of direct fetal biomarkers that provide information on both the magnitude and timing of fetal exposure to multiple chemicals has been a major barrier [4]. Multiplexed mass-spectrometry methods have been recently applied to the tooth-matrix to reconstruct prenatal and early postnatal exposure to thousands of compounds, including environmental chemicals and their internal reaction products [5]. For example, neurodevelopmental deficits from excessive exposure to manganese were uncovered in children exposed to pesticides high in this metal.…”
Section: Tooth-matrix Biomarkers As Windows Into Early Life Developmentmentioning
confidence: 99%
“…For example, neurodevelopmental deficits from excessive exposure to manganese were uncovered in children exposed to pesticides high in this metal. Recently, we also showed that a broad range of homeostatic disruptions caused by physical trauma, infections and even psychosocial stressors, such as separation from the mother, are captured in the dentine matrix [5] [6]. …”
Section: Tooth-matrix Biomarkers As Windows Into Early Life Developmentmentioning
confidence: 99%
See 2 more Smart Citations